The Application Of Model 7Ps Marketing Mix At STKIP Weetebula - kii Yape Wilhelmus (Jurnal Edukasi Sumba (JES), 2019)
This paper describes the marketing planning of STKIP Weetebula to increase the number of STKIP Weetebula students according to the Medium and Long Term Development Strategy of STKIP Weetebula.The first part of this paper explains about marketing, marketing model management, stakeholder analysis and continues with explanations about STKIP Weetebula.In the second part, the key stakeholders are defined using the stakeholder matrix. Once key stakeholders are determined, the next step is to make marketing planning for key stakeholders. There are several marketing planning models that can be used by education institutions to develop a marketing planning. STKIP Weetebula choose the 7 P marketing mix because it is a marketing planning model that is quite widely used in higher education organizations and considered suitable for educational institutions such as STKIP Weetebula.